2003
DOI: 10.1007/bf02783420
|View full text |Cite
|
Sign up to set email alerts
|

Games of incomplete information, ergodic theory, and the measurability of equilibria

Abstract: We present an example of a one-stage three player game of incomplete information played on a sequence space {0, 1} Z such that the players' locally finite beliefs are conditional probabilities of the canonical Bernoulli distribution on {0, 1} Z , each player has only two moves, the payoff matrix is determined by the 0-coordinate and all three players know that part of the payoff matrix pertaining to their own payoffs. For this example there are many equilibria (assuming the axiom of choice) but none that invol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
60
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 10 publications
0
60
0
Order By: Relevance
“…belongs), or more generally, by a -…eld z i of measurable sets (events) in (in which case i knows, given any event in z i ; whether it has occurred). It was shown by Simon (2003) that Bayesian Nash equilibrium (BNE) may fail to exist in games with di¤erential information, as a result of discontinuity of the expected payo¤ function in Bayesian strategies of all players simultaneously. The situation changes, however, when attention is con…ned to two-person zero-sum games with di¤erential information.…”
Section: Introductionmentioning
confidence: 99%
“…belongs), or more generally, by a -…eld z i of measurable sets (events) in (in which case i knows, given any event in z i ; whether it has occurred). It was shown by Simon (2003) that Bayesian Nash equilibrium (BNE) may fail to exist in games with di¤erential information, as a result of discontinuity of the expected payo¤ function in Bayesian strategies of all players simultaneously. The situation changes, however, when attention is con…ned to two-person zero-sum games with di¤erential information.…”
Section: Introductionmentioning
confidence: 99%
“…13 Assuming countability allows us to avoid measurability issues, in particular regarding existence of Bayesian Nash equilibria (cf. Simon [21]). …”
Section: Incomplete Information Perturbationsmentioning
confidence: 99%
“…Weinstein and Yildiz [24] show that for any complete information type in the universal type space 21 and any rationalizable action profile a * of this game, there exist a dominance-solvable incomplete information game and a sequence of types drawn from this game such that (1) this sequence converges to the complete information type (with respect to the product topology in the universal type space) and (2) each type of the sequence plays a * , while they are not concerned with priors but working directly with interim beliefs. Our construction in Lemma 3.4 shows that, by attaching heterogeneous priors appropriately, such a dominance solvable incomplete information game can be made an (ε, N)-perturbation (where ε can be arbitrarily small and N arbitrarily large).…”
Section: Proof Of Proposition 33mentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, recently, Simon [13] showed that, there may be problem with the existence of measurable equilibrium of the games with incomplete information. Hence, a model, in which , the beliefs of the players are modeled by probability measures, is not necessarily appropriate for some problems.…”
Section: Example 21mentioning
confidence: 99%